Functional requirements of a mobile‐based application for stroke self‐management: A Delphi study - Hamidreza Tadayon; Seyed Ali Masoud; Ehsan Nabovati; Hossein Akbari; Mehrdad Farzandipour; Masoud Babaei (Healthcare Technology Letters, 2022)
Abstract This study aimed to determine the functional requirements of a self‐management mobile application for stroke survivors. For extracting the initial functional requirements, a literature review as well as interviews with 17 patients and caregivers were done. The results were analyzed using the content analysis method. The initial extracted requirements were then provided to the specialists by the Delphi technique to determine the final functional requirements. Content validity ratio (CVR) and content validity index (CVI) were calculated according to the Lawshe model. Criteria for item approval included CVR > 0.49 and CVI > 0.79. Finally, the approved items were turned into a five‐point Likert scale questionnaire and were then provided to 53 experts and items with a mean score higher than 3.75 were approved. Functional requirements including creating a user account, educational material, support services, providing reminders and alerts for drugs administration and physician appointments, and rehabilitation exercises (to improve balance, upper and lower extremities rehabilitation, and activities of daily living (ADLs)) were approved. Most of the approved functional requirements were related to rehabilitation exercises for improving upper limb motor function. The experts did not approve the requirements for using splints and slings or the recommendation to take some medications.